The Influence of Raw Material Price, Distribution Cost and Exchange Rate on Export Volume of Adidas T-Shirts at PT. Apparel One Indonesia 2 - Amanda - Hapsari; Karnowahadi - Karnowahadi; Agus - Suratno (Politeknik Negeri Semarang, 2020)
Based on the background of the research, the cause of Adidas's export volume which fluctuates every month from 2016-2019 is unknown yet. Factors that could be the cause of these fluctuations are the raw material price, distribution cost, and exchange rates.The research aims to analyze the effect of Raw Material Price on export volume, the effect of Distribution Cost on export volume, the effect of Exchange Rate on Export Volume, and the effect of Raw Material Price, Distribution Cost, and Exchange Rate on export volume of Adidas at PT. Apparel One Indonesia 2 and to find out how many contributions of all independent variables to dependent variable. This research is an explanatory research with quantative approach. Multiple Linear Regression Analysis method is used in this study equipped with the Descriptive Statistics Test, Classic Assumption Test, Correlation Coefficients, Coefficient of Determination, F-Test and T-Test. Data used in this study are secondary data which are obtained by doing a literature review and observation, and collected from PT Apparel One Indonesia 2 and Bank of Indonesia from January 2016-December 2018. The output from this research shows that three independent variables which are used have a significant effect on the export volume of Adidas at PT. Apparel One Indonesia 2. Partially, it shows that raw material price influence negative and insignificant to the export volume. For distribution cost, the result shows negatively and significantly influence on export volume. The other output explained that exchange rate influence positive and insignificant to the Adidas's export volume. The result shows that only one variable has a significant influence on export volume.